Zeta potential in colloid science : principles and applications - Hunter, Robert J. (Colloid science., 1988)
Zeta Potential in Colloid Science: Principles and Applications covers the concept of the zeta potential in colloid chemical theory. The book discusses the charge and potential distribution at interfaces; the calculation of the zeta potential; and the experimental techniques used in the measurement of electrokinetic parameters. The text also describes the electroviscous and viscoelectric effects; applications of the zeta potential to areas of colloid science; and the influence of simple inorganic ions or more complex adsorbates on zeta potential. Physical chemists and people involved in the stu.